A Fast and Validated Mass Spectrometry Method for the Evaluation of Human Serum Albumin Structural Modifications in the Clinical Field. Issue 6 (December 2013) - Naldi, M.; Giannone, F.A.; Baldassarre, M.; Domenicali, M.; Caraceni, P.; Bernardi, M.; Bertucci, C.
A relatively fast analytical method for the identification and quantification of the post-transcriptional changes (PTCs) occurring in circulating human serum albumin (HSA) was developed. HSA is the most abundant protein in plasma and it represents the main determinant of plasma oncotic pressure, thus being the main modulator of fluid distribution between body compartments. Cirrhotic patients have low levels of HSA. Moreover, recent studies have demonstrated that during liver cirrhosis HSA presents PTCs affecting its properties. The HSA isoforms derived from these modifications could represent promising biomarkers for liver disease. Human plasma samples were collected from a cirrhotic patient (CH) and from an aged-matched non-cirrhotic subject (CT), purified by reverse-phase chromatography and analysed by an electrospray ionization quadrupole time-of-flight (ESI-Q-ToF) spectrometer. The deconvoluted ESI mass spectra from healthy subjects were all characterized by peaks attributed to mercaptoalbumin, nitrosylated, cysteinylated, glycated and N-terminal truncated HSA isoforms. The relative abundance of each isoform was derived and transformed into a relative per cent amount and the results were compared to those obtained analysing HSA from a CH plasma. The method was validated in terms of intra-day and inter-day reproducibility, both for quantitative results and PTCs molecular weight determination. The optimized method resulted in being effective in disclosing changes in HSA isoforms relative abundance and then it could be used for the systematic screening of cirrhotic patients to identify promising new biomarkers for liver diseases.